EFIKASI RUTE VAKSIN Aeromonas hydrophila ASB-01 PADA IKAN GABUS (Ophiocephalus striatus) - Olga Olga; Fatmawati Fatmawati (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aims to determine the vaccine A.hydrophila ASB-01 is effective forthe control of MAS on snakehead fish. Effectiveness of vaccination was evaluated through the antibody titer, survival, RPS (relative percent survival) and RWK (meantime of death). The study consisted of 5 treatments (immersion vaccination (R), oral(O), intramuscular injection (IM), intraperitoneal injection (IP) and control (PBS pH7.0) with 3 replications. Vaccination doses were 107 cells / ml. Booster vaccination after 14 days later. Dose is equal to the initial vaccination. Furthermore, the next day14 fish were challenged with A.hydrophila ASB-01. To obtain data on antibody titerblood draw done at the time before being vaccinated, shortly before the booster vaccination and 14 days after the booster vaccination. Challenged fish were observedfor 14 days to obtain data on survival, RPS and RWK. The result showed that allthese vaccines may increase the antibody titer, but the highest antibody titers obtained from fish vaccinated injection. Survival rates were vaccinated IM (84.47%), IP(82.20%), R (42.27%), O (42.20%) and controls (13.13%). RPS to IM (82.08%), IP(79.46%), R (33.38%), O (33.31%), while RWK through the IP (3.63 days), IM(79.46 3.57 days), R (2.46 days), O (1.85 days) and controls (1.03 days). Effective vaccination route is through injection.